Estimation of food threshold for families of minimum wage earners in the National Capital Region - Luna, Ma. Veritas C. Fojas; Bongga, Demetria C. (1988)
To develop a sensitive methodology to estimate the food threshold of families of minimum wage earners in the National Capital Region, 101 households from low-income urban communities were interviewed. Other socio-economic factors related to food consumption and expenditure were also analyzed. Results showed no significant differences in food expenditure when households were grouped by household size. However, households with heads engaged in heavy occupational activity had significantly lower food expenditure than those with heads engaged in either light or moderate occupational activity. The energy intake of all households were generally low, however households with heads engaged in either light or moderate occupational activity appeared to have better energy intakes than those with heads engaged in heavy occupational activity. Although no significant differences in nutritional status of participants were observed when grouped according to household size and occupational activity of heads to which they belonged, it appeared that more preschoolers were moderately underweight among households whose heads engaged in heavy occupational activity. Estimation of food threshold among the study households was based on three correlates: diet rating, food expenditure and calorie adequacy of households, in two regression equations. Food threshold was estimated as the per caput food expenditure that corresponded to a diet rating of an intake that was 100% adequate in calories. The method used is considered quite sensitive because it considered variables which significantly affect the food threshold.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Cost and standard of living -- Philippines -- Manila metropolitan area; Wages -- Minimum wages -- Philippines -- Manila metropolitan area